2021
DOI: 10.3390/app112411726
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Sensitivity of FeGa Thin-Film Coated SAW Current Sensor

Abstract: A surface acoustic wave (SAW) device is proposed for sensing current by employing the patterned FeGa thin film as the sensitive interface. The layered media structure of FeGa/SiO2/LiNbO3 was established to reveal the working principle of the sensors, and an SAW chip patterned by delay-line and operating at 150 MHz was fabricated photolithographically on 128° YX LiNbO3 substrate. The FeGa thin film with a larger magnetostrictive coefficient was sputtered onto the acoustic propagation path of the SAW chip to bui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…Combining (3) to ( 6) with (1), (2) and the condition 𝛻 • 𝐷 = 0, we can express the constitutive (7) in index form for the AlN piezoelectric material [4].…”
Section: Mathematical Model For Fem Simulationmentioning
confidence: 99%
See 2 more Smart Citations
“…Combining (3) to ( 6) with (1), (2) and the condition 𝛻 • 𝐷 = 0, we can express the constitutive (7) in index form for the AlN piezoelectric material [4].…”
Section: Mathematical Model For Fem Simulationmentioning
confidence: 99%
“…Common constructions for magnetic SAW sensors usually have a magnetic sensitive materials, an intermediate layers, an electrodes and a piezoelectric substrates (magnetic sensitive materials/intermediate layers/electrodes/piezoelectric substrates). Several recent studies indicate that common magnetostrictive sensitive materials, including Ni, FeGa, FeCo, and FeNi, have been combined with quartz and LiNbO3 piezoelectric substrates to measure magnetic field intensity and current with high sensitivity [4]- [6], [10]- [17]. The results show that the thickness of the magnetic materials significantly [4], [11], [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The magnetosensitive film is the key influencing factor of the performance of the SAW magnetic field sensor. Typical magnetosensitive materials mostly constitute magnetostrictive materials such as FeCo [7,8], FeNi [9], FeGa [10], FeGaB [11], and AlScN [12]. The combination of FeCoSiB films with SAW technology has in recent years been found to have the potential to achieve increased magnetic field detection sensitivity and ultra-fast response speed owing to its excellent magnetic and mechanical properties [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The shear modulus increased from 45 GPa to 57 GPa at magnetic field saturation [18]. To improve the detection sensitivity and reduce the hysteresis error, Wang et al designed and fabricated SAW devices with different thin-film patterns (dot, grating, and membrane), and found that the dot-like thin film structure can increase the magnetostrictive effect by fully releasing the internal coericivity of the magnetistrictive [10], and a large current sensitivity (37.9 k A −1 ) can be achieved [19]; as an available way allowing enhancement of adhesion, a Cr thin film was employed as the transition-layer to weaken the mechanical fatigue [20]. Kittmann et al tested SAW magnetic field sensors with different magnetostrictive layer thicknesses and found that the device insertion loss increased from 17 dB to 21 dB with increasing thickness [16].…”
Section: Introductionmentioning
confidence: 99%